Evaluation of Railway Infrastructure on Track Quality Index (TQI) Based Track Quality (Cross of Mandai - Garongkong) 2024 - Wibowo, Arief Hadi; Desy, Natsar; Gusty, Sri (Universitas Ibn Khaldun Bogor, 2026)
Infrastructure quality greatly affects the speed, comfort, and safety of train travel. High speed can cause damage to the railroad track which can cause a decrease in the TQI value and increase the risk of train accidents. This study aims to analyze the factors influencing train speed, analyze the speed of railway facilities on track quality based on Track Quality Index, and analyze optimization strategies to keep the Track Quality Index (TQI) within the operating speed threshold in 2024. The method used in this research is mix method. The results showed that the factors affecting train speed across Mandai-Garongkong are the condition of the rail line and Track Quality Index (TQI), track geometry and rail infrastructure, characteristics of rolling stock, external environment, and operational management and speed regulation, so that the optimization strategy needed to enable optimal operational speed is the implementation of preventive and corrective maintenance strategies, real-time TQI monitoring with observation technology, and operational management based on observation results. Based on the calculation of the Track Quality Index (TQI) value on each track plot, it is found that the average TQI value is above 10, while the average operational speed is above 30 km/h, although the average TQI value is above 10, the operational speed can still be maintained above 30 km/h. It is recommended to immediately bring in facilities with speeds capable of maximizing the existing TQI value on the South Sulawesi crossing.